A causal supervisory control strategy for optimal control of a heavy-duty Diesel engine with SCR aftertreatment. (February 2022) - van Dooren, Stijn; Amstutz, Alois; Onder, Christopher H.
Abstract: Diesel engines continue to be the prime movers in heavy-duty and non-road applications. Optimising and controlling the engine and its exhaust-gas aftertreatment system (ATS) for low fuel consumption and low pollutant emissions remains a challenging task. Typically, the engine and ATS are calibrated separately and based on engineering experience. In order to exploit the full potential of the overall system, a so-called supervisory control strategy can be used. In this paper, we develop such a strategy based on Pontryagin's minimum principle and show that its performance is close to the globally optimal solution. Compared to similar approaches, our concept does not require the optimal control problem to be solved online. Instead, we derive a simple, causal, and near-optimal control law that is easy to implement and tune. We present experimental results from the engine test-bench to demonstrate the practical feasibility and effectiveness of the proposed approach. Furthermore, we show how the strategy can be adapted online using sensor feedback in order to meet a given emission target during arbitrary and unknown engine operation.